Conversion to a rearfoot strike pattern during running for prevention of recurrent calf strains: A case report. (January 2020) - Baquet, Ari; Mazzone, Brittney; Yoder, Adam; Farrokhi, Shawn
Abstract: Background: Running-related injuries are prevalent musculoskeletal complaints in the United States military. Although, run retraining is an extensively researched method for reducing pain and improving function in runners, its clinical utility remains low. Case description: The patient had a seven-year history of recurrent right calf strains. Prior conventional physical therapy failed to resolve symptoms. A biomechanical running analysis revealed a right forefoot strike during running. The patient underwent run retraining that included real-time visual feedback and a faded feedback strategy focused on converting foot strike pattern to rearfoot. Running mechanics were reassessed post-training, and at one and six months post-training. Outcomes: Foot strike pattern was successfully converted to rearfoot strike and was maintained up to six months post-training. Reductions in peak ankle dorsiflexion moment and dorsiflexion velocity were noted up to six months post-training. Self-reported function also improved by 20–30% and no calf strains were reported up to six months post-training. Discussion: This case report details the clinical reasoning and evidence-informed interventions involved in treatment of a patient with chronic calf strains. The management strategy was intended to reduce eccentric calf demands, which allowed the patient to tolerate increased running frequency without any further episodes of calf strains up to six months post-training.